Care for the Dying: A Kübler-Ross Critique - Kuykendall, George (Theology today, 1981)
“Christians are not … to delude people as to their capacity to master death. Christian care precludes giving them over to their own resources, in the fantasy that those resources may be adequate. Rather, Christian care for the dying will seek to sustain them as they suffer the ravages of living and dying. We must care for them as long and as well as we can, identifying their hurts and healing them if we are able, surrounding and enfolding them with reminders of the care that God bears toward them.”